Disulfide Bond-Containing Ajoene Analogues As Novel Quorum Sensing Inhibitors of Pseudomonas aeruginosa - Fong, July (2017)
Since its discovery 22 years ago, the bacterial cell-to-cell communication system, termed quorum sensing (QS), has shown potential as antipathogenic target. Previous studies reported that ajoene from garlic inhibits QS in opportunistic human pathogen Pseudomonas aeruginosa. In this study, screening of an in-house compound library revealed two sulfur-containing compounds which possess structural resemblance with ajoene and inhibit QS in bioreporter assay. Following a quantitative structure–activity relationship (SAR) study, 25 disulfide bond-containing analogues were synthesized and tested for QS inhibition activities. SAR study indicated that the allyl group could be replaced with other substituents, with the most active being benzothiazole derivative (IC50 = 0.56 μM). The compounds were able to reduce QS-regulated virulence factors (elastase, rhamnolipid, and pyocyanin) and successfully inhibit P. aeruginosa infection in murine model of implant-associated infection. Altogether, the QS inhibition activity of the synthesized compounds is encouraging for further exploration of novel analogues in antimicrobial drug development.